Difluoro vulcanized phenyl silicon-based rubber and preparation method thereof
By using bisfluorosulfide benzene silicone-based rubber, the problem of existing fluorosilicone rubber failure or falling off under high temperature, high pressure and hydrogen sulfide conditions is solved, and higher high temperature resistance, hydrogen sulfide and wear resistance are achieved, extending the service life of the rotary drilling tool and improving the working efficiency.
Patent Information
- Application Number
- CN202411702126.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
AI Technical Summary
The seals used in existing fluorosilicone rubber for rotary drilling tools are prone to failure or fall off under harsh conditions such as high temperature, high pressure and hydrogen sulfide, resulting in failure or fall off of sealing materials during drilling.
Bisfluorosulfide benzene silicone-based rubber is used, with a molecular weight between 8000 and 12000, a fluorine content of 1.4%-2.0%, a phenyl content of 18%-24%, and a hydrogen content of 2.1%-3.0%. Through specific vulcanization conditions and binder combination, the rubber's high temperature resistance, hydrogen sulfide and wear resistance are improved.
Bifluorosulfide benzene silicon-based rubber exhibits excellent high-temperature resistance, hydrogen sulfide resistance, wear resistance and impact resistance under high temperature and high pressure conditions, extending the service life of rotary drilling tools, reducing the complex accident rate of deep well sections, and improving operating efficiency.
Smart Images

Figure BDA0005153594980000021 
Figure BDA0005153594980000131 
Figure BDA0005153594980000141
Abstract
Description
Technical Field
[0001] The invention relates to the field of fluorosilicone rubber, and in particular to a difluorosulfurized phenylsilicone-based rubber and a preparation method thereof. Background Art
[0002] During deep shale gas drilling, the seals of rotary drilling tools are prone to failure under harsh conditions such as hydrogen sulfide, high temperature, and high speed. At present, the sealing materials used in rotary drilling tools, such as rubber, polytetrafluoroethylene, butyl rubber, fluororubber, and silicone rubber, frequently fail or fall off when the temperature exceeds 170°C. Now a new sealing material is urgently needed to solve the problem of sealing material failure or falling off during drilling. Summary of the invention
[0003] The object of the present invention is to provide a difluorosulfurized phenyl silicone rubber and a preparation method thereof, so as to solve the problem that the existing fluorosilicone rubber is prone to failure or falling off when used for sealing parts of rotary drilling tools.
[0004] The embodiments of the present invention are implemented by the following technical solutions:
[0005] A difluoro-sulfurized phenyl silicone rubber, the difluoro-sulfurized phenyl silicone rubber has a molecular weight of 8000-12000, a fluorine content of 1.4%-2.0%, a phenyl content of 18%-24%, and a hydrogen content of 2.1%-3.0%;
[0006] The molecular structure of the difluorosulfurized phenyl silicone rubber is shown in (I), wherein n in formula (I) is 16-25 and m is 13-20;
[0007]
[0008] Preferably, the fluorine content of the difluorosulfurized phenyl silicone rubber is 1.7%, the phenyl content is 21%, and the hydrogen content is 2.6%.
[0009] A method for preparing the difluorosulfurized phenyl silicone rubber comprises:
[0010] S100, 110-120 parts of m-difluorostyrene, 30-35 parts of reinforcing agent, 2-5 parts of vulcanizing agent, 8-10 parts of ferric oxide, 1-1.2 parts of structure control agent, and 3-5 parts of high temperature resistant agent are added into an open mill several times, and mixed to obtain a primary rubber;
[0011] S200, vulcanizing the pre-made rubber in a vulcanizer to obtain a difluorobenzene sulfide test piece, wherein the thickness of the test piece after the difluorobenzene sulfide and silicone-based rubber mixed rubber is molded and vulcanized is 2.6 mm;
[0012] S300, after the benzene bis(fluorosulfide) test piece is coated with an adhesive, the benzene bis(fluorosulfide) test piece is stacked with a silicone rubber compound, and the benzene bis(fluorosulfide) silicone-based rubber is obtained after mold closing and vulcanization.
[0013] Preferably, the vulcanization conditions in S200 are: vulcanization temperature is 165-180° C., pressure is 8-12 MPa, and vulcanization time is 30-35 min.
[0014] Vulcanization is a key step in rubber processing, which refers to the process of cross-linking linear or branched rubber molecules into a three-dimensional network structure through chemical reactions. The present invention adopts a reasonable vulcanization temperature to adjust the vulcanization rate and the degree of vulcanization to ensure the best vulcanization effect. The limitation of the vulcanization time ensures the appropriate cross-linking density between rubber molecules. Too short a time may lead to insufficient vulcanization, resulting in insufficient product strength; too long a time may cause over-vulcanization, resulting in hardening of the material and increased brittleness. Therefore, precise control of the vulcanization time is crucial to ensure product quality. Applying appropriate pressure during the vulcanization process can help remove the air in the mold, prevent the generation of bubbles, and ensure that the product surface is smooth and defect-free. In addition, pressure can also promote the rubber to fill the mold better and improve the dimensional accuracy of the product.
[0015] Preferably, the vulcanization conditions in S300 are: vulcanization temperature is 175-195° C., pressure is 8-12 MPa, and vulcanization time is 18-23 min.
[0016] Preferably, the binder includes 55-65 parts of Chemlock 607, 25-35 parts of Chemlock 608 and 5-15 parts of Chemlock 205 in parts by weight.
[0017] Chemlok adhesive has excellent bonding properties and can achieve strong bonding on a variety of substrates, including metals, plastics, composite materials, etc. The present invention compounded different types of Chemlok adhesives to make the adhesive show higher bonding strength when bonding the bis(fluorosulfide)benzene test piece and the silicone rubber compound. In addition, different Chemlok adhesives differ in weather resistance and chemical resistance. Through compounding, adhesives with complementary properties can be selected to improve the durability and corrosion resistance of the final product. The curing time of the adhesive is also adjusted by compounding the adhesive, making it more compatible with the mold vulcanization process.
[0018] Preferably, the structure control agent comprises, by weight: 25-30 parts of organosilane, 45-55 parts of dimethyldiethoxysilane and 20-24 parts of disodium silyl ether.
[0019] The structure control agent provided by the present invention can reduce the Mooney viscosity of the rubber, which makes the rubber easier to mix, plasticize and shape. The low-viscosity rubber requires less energy during processing and has higher production efficiency. The structure control agent can make the rubber softer and more plastic, thereby improving its processing performance. This is particularly important for processes such as extrusion, calendering and injection molding, which can reduce equipment wear and energy consumption and improve production efficiency. The structure control agent helps to improve the dispersibility of fillers, such as reinforcing agents, in the rubber matrix, thereby improving the physical properties of the rubber. The structure control agent provided by the present invention can also affect the vulcanization process of the rubber, regulate the vulcanization speed and the degree of vulcanization, help optimize the vulcanization conditions, and improve the uniformity and consistency of the product. It can also improve the flexibility and elasticity of the rubber at low temperatures, heat resistance and aging resistance, surface finish, etc.
[0020] Preferably, the vulcanizing agent comprises, by weight: 30-35 parts of dipentadienyl vulcanizing agent, 38-42 parts of fluororubber vulcanizing agent, 7-9 parts of fluororubber vulcanizing agent accelerator BPP, 8-12 parts of 1,4-butanediamine and 8-12 parts of 1,6-hexanediamine.
[0021] The present invention adjusts the vulcanization speed and the vulcanization degree by compounding the vulcanizing agent, so that the reaction can achieve an ideal vulcanization effect in a relatively short time, and can also improve the wear resistance, impact resistance, heat resistance and aging resistance of the product.
[0022] Preferably, in parts by weight, the reinforcing agent comprises: 40-50 parts of carbon black and 50-60 parts of silane coupling agent.
[0023] Reinforcers can improve the strength, wear resistance, aging resistance and processing performance of rubber materials to achieve a reinforcing effect. Carbon black can significantly improve the physical and mechanical properties of rubber, especially wear resistance and tensile strength. Silane coupling agents significantly improve the properties of rubber by forming chemical bonds or physical adsorption between rubber and inorganic fillers. Silane coupling agents can improve the dispersibility of fillers, such as carbon black. They can also improve the compatibility of various additives or fillers in the rubber matrix, thereby improving mechanical properties. The interface layer formed by silane coupling agents can also improve the aging resistance and chemical resistance of the product.
[0024] Preferably, in parts by weight, the high temperature resistant agent comprises: 45-55 parts of antioxidant 626, 25-35 parts of antioxidant 1076, and 18-24 parts of polytetrafluoroethylene powder.
[0025] High temperature resistant agents are mainly used to improve the heat resistance, oxidation resistance and physical properties of rubber products under high temperature conditions. Antioxidants prevent or slow down oxidation reactions by capturing free radicals, thereby preventing the breakage and cross-linking of rubber molecular chains and maintaining the physical properties of rubber.
[0026] Tetrafluoroethylene micropowder has extremely high heat resistance and can be used for a long time at temperatures up to 260°C, and can even withstand higher temperatures (above 300°C) for a short period of time. When added to rubber, it can significantly improve the heat resistance of these materials. Tetrafluoroethylene micropowder has excellent resistance to most chemicals, including acids, alkalis, solvents and many organic compounds. This allows materials with added tetrafluoroethylene micropowder to maintain good performance in corrosive environments. Tetrafluoroethylene micropowder has a very low coefficient of friction and can form a lubricating film on the surface of the material, reducing friction and wear, and improving the wear resistance and self-lubricating properties of rubber products. It is particularly suitable for applications that require low friction and high wear resistance. Tetrafluoroethylene micropowder can act as an internal lubricant to reduce friction between rubber molecules and improve the fluidity and processing properties of the material.
[0027] The composition of tetrafluoroethylene micropowder can be: 70wt% of microparticles with a particle size of 0.071mm, 10wt% of microparticles with a particle size of 0.063mm, 10wt% of microparticles with a particle size of 0.088mm, 5wt% of microparticles with a particle size of 0.09mm, and 5wt% of microparticles with a particle size of 0.1mm. The compounding of microparticles of different particle sizes can make the performance between the microparticles complementary. Fine-particle PTFE micropowder has a larger specific surface area and is easier to disperse evenly in the rubber matrix, while coarse-particle PTFE micropowder can provide better lubricity and wear resistance. By compounding PTFE micropowders of different particle sizes, more uniform dispersion can be achieved, agglomeration can be avoided, and the overall performance of the material can be improved. Fine-particle PTFE micropowder can form a uniform lubricating film on the surface of the material to reduce friction; while coarse-particle PTFE micropowder can provide a more lasting lubrication effect inside the material. Compounding PTFE micropowders of different particle sizes can simultaneously improve the surface lubricity and internal lubricity of the material, achieving a more comprehensive lubrication effect. Coarse-grained PTFE powder has high hardness and wear resistance, which can significantly improve the wear resistance of the material; while fine-grained PTFE powder can fill the tiny pores on the surface of the material, reduce wear points, significantly improve the wear resistance and abrasion resistance of the material, and extend the service life. PTFE powders of different particle sizes have different stability at high temperatures. Fine-grained PTFE powder can be evenly distributed in the material faster and improve the overall heat resistance; while coarse-grained PTFE powder can provide more stable structural support at high temperatures, thereby improving the stability and heat resistance of the material in high temperature environments and preventing performance degradation caused by high temperatures. Fine-grained PTFE powder can improve the flexibility and elasticity of the material, while coarse-grained PTFE powder can enhance the rigidity and strength of the material. By compounding PTFE powders of different particle sizes, the physical properties of the material, such as tensile strength, tear strength and elastic modulus, can be optimized, making it perform better in different application scenarios.
[0028] The present invention has at least the following beneficial effects:
[0029] The present invention improves the preparation method of the difluorosulfurized phenyl silicone rubber so that the molecular weight, fluorine content, phenyl content and hydrogen content of the difluorosulfurized phenyl silicone rubber are within specific ranges. The product has excellent performance in high temperature resistance, hydrogen sulfide resistance, wear resistance and impact resistance. When the product is used as a sealing material for a rotary drilling tool, the average number of trips can be shortened, the service life of the rotary drilling tool can be increased, and the ground cooling system of the drilling fluid can be reduced or not used, thereby improving the timeliness and efficiency of the operation and significantly reducing the rate of complex accidents in deep well sections. DETAILED DESCRIPTION
[0030] In order to make the purpose, method scheme and advantages of the embodiments of the present invention clearer, the method scheme in the embodiments of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0031] Embodiment 1: A method for preparing difluorosulfurized phenyl silicone rubber, comprising:
[0032] S100, 110 parts of m-difluorostyrene, 30 parts of reinforcing agent, 2 parts of vulcanizing agent, 8 parts of ferric oxide, 1 part of structure control agent, and 3 parts of high temperature resistant agent are put into an open mill in 10 times, and the roller distance is controlled at 4 mm during mixing, and the initial rubber is obtained by mixing; in parts by weight, the structure control agent includes: 25 parts of organic silane, 45 parts of dimethyldiethoxysilane and 20 parts of dimethylsilyl ether; in parts by weight, the vulcanizing agent includes: 30 parts of dipentadienyl vulcanizing agent, 38 parts of fluororubber vulcanizing agent, 7 parts of fluororubber vulcanizing agent accelerator BPP, 8 parts of 1,4-butanediamine and 8 parts of 1,6-hexanediamine diamine; in parts by weight, the reinforcing agent includes: 40 parts of Cabot carbon black, 50 parts of silane coupling agent LD-560; in parts by weight, the high temperature resistant agent includes: 45 parts of Lianlong antioxidant 626, 25 parts of Beijing Jiyi antioxidant 1076, and 18 parts of polytetrafluoroethylene micropowder, and the composition of the polytetrafluoroethylene micropowder is: 70wt% of particles with a particle size of 0.071mm, 10wt% of particles with a particle size of 0.063mm, 10wt% of particles with a particle size of 0.088mm, 5wt% of particles with a particle size of 0.09mm, and 5wt% of particles with a particle size of 0.1mm;
[0033] S200, after putting the primary rubber into the mold, vulcanizing it in a vulcanizer to obtain a difluorobenzene sulfide test piece with a thickness of 0.7 mm; the vulcanization temperature is 165° C., the pressure is 8 MPa, and the vulcanization time is 30 min;
[0034] S300. After the benzene fluoride sulfide test piece is coated with the adhesive, the benzene fluoride sulfide test piece is stacked with the silicone rubber compound, and after mold vulcanization, a benzene fluoride sulfide silicone-based rubber test piece with a thickness of 2.6 mm is obtained; the vulcanization temperature is 175°C, the pressure is 8 MPa, and the vulcanization time is 18 min; in parts by weight, the adhesive includes 55 parts of Chemlock 607, 25 parts of Chemlock 608 and 5 parts of Chemlock 205.
[0035] Embodiment 2: A method for preparing difluorosulfurized phenyl silicone rubber, comprising:
[0036] S100, 120 parts of m-difluorostyrene, 35 parts of reinforcing agent, 5 parts of vulcanizing agent, 10 parts of ferric oxide, 1.2 parts of structure control agent and 5 parts of high temperature resistant agent are put into an open mill in 10 times, and the roller distance is controlled at 4 mm during mixing, and the initial rubber is obtained by mixing; in parts by weight, the structure control agent includes: 30 parts of organic silane, 55 parts of dimethyldiethoxysilane and 24 parts of dimethylsilyl ether; in parts by weight, the vulcanizing agent includes: 35 parts of dipentadienyl vulcanizing agent, 42 parts of fluororubber vulcanizing agent, 9 parts of fluororubber vulcanizing agent accelerator BPP, 12 parts of 1,4-butanediamine and 12 parts of 1,6 -hexanediamine; in parts by weight, the reinforcing agent includes: 50 parts of Cabot carbon black, 60 parts of silane coupling agent LD-560; in parts by weight, the high temperature resistant agent includes: 55 parts of Lianlong antioxidant 626, 35 parts of Beijing Jiyi antioxidant 1076, and 24 parts of polytetrafluoroethylene micropowder, and the composition of the polytetrafluoroethylene micropowder is: 70wt% of particles with a particle size of 0.071mm, 10wt% of particles with a particle size of 0.063mm, 10wt% of particles with a particle size of 0.088mm, 5wt% of particles with a particle size of 0.09mm, and 5wt% of particles with a particle size of 0.1mm;
[0037] S200, after putting the primary rubber into the mold, vulcanizing it in a vulcanizer to obtain a difluorobenzene sulfide test piece with a thickness of 0.7 mm; the vulcanization temperature is 180° C., the pressure is 12 MPa, and the vulcanization time is 35 min;
[0038] S300. After the benzene fluoride sulfide test piece is coated with the adhesive, the benzene fluoride sulfide test piece is stacked with the silicone rubber compound, and after mold vulcanization, a benzene fluoride sulfide silicone-based rubber test piece with a thickness of 2.6 mm is obtained; the vulcanization temperature is 195°C, the pressure is 12MPa, and the vulcanization time is 23min; in parts by weight, the adhesive includes 65 parts of Chemlock 607, 35 parts of Chemlock 608 and 15 parts of Chemlock 205.
[0039] Embodiment 3: A method for preparing difluorosulfurized phenyl silicone rubber, comprising:
[0040] S100, 115 parts of m-difluorostyrene, 33 parts of reinforcing agent, 3 parts of vulcanizing agent, 9 parts of ferric oxide, 1.1 parts of structure control agent, and 4 parts of high temperature resistant agent are put into an open mill in 10 times, and the roller distance is controlled at 4 mm during mixing, and the initial rubber is obtained by mixing; in parts by weight, the structure control agent includes: 28 parts of organic silane, 50 parts of dimethyldiethoxysilane and 22 parts of dimethylsilyl ether; in parts by weight, the vulcanizing agent includes: 32 parts of dipentadienyl vulcanizing agent, 40 parts of fluororubber vulcanizing agent, 8 parts of fluororubber vulcanizing agent accelerator BPP, 10 parts of 1,4-butanediamine and 10 parts of 1,6 -hexanediamine; in parts by weight, the reinforcing agent includes: 45 parts of Cabot carbon black, 55 parts of silane coupling agent LD-560; in parts by weight, the high temperature resistant agent includes: 50 parts of Lianlong antioxidant 626, 30 parts of Beijing Jiyi antioxidant 1076, and 20 parts of polytetrafluoroethylene micropowder, and the composition of the tetrafluoroethylene micropowder is: 70wt% of particles with a particle size of 0.071mm, 10wt% of particles with a particle size of 0.063mm, 10wt% of particles with a particle size of 0.088mm, 5wt% of particles with a particle size of 0.09mm, and 5wt% of particles with a particle size of 0.1mm;
[0041] S200, after putting the primary rubber into the mold, vulcanizing it in a vulcanizer to obtain a bis(fluorobenzene)sulfide test piece with a thickness of 0.7 mm; the vulcanization temperature is 172° C., the pressure is 10 MPa, and the vulcanization time is 33 min;
[0042] S300. After the bis(fluorobenzene)sulfide test piece is coated with the adhesive, the bis(fluorobenzene)sulfide test piece and the silicone rubber compound are stacked, and after mold vulcanization, a bis(fluorobenzene)sulfide silicone-based rubber test piece with a thickness of 2.6 mm is obtained; the vulcanization temperature is 184°C, the pressure is 10 MPa, and the vulcanization time is 20 min; in parts by weight, the adhesive includes 60 parts of Chemlock 607, 30 parts of Chemlock 608 and 10 parts of Chemlock 205.
[0043] Comparative Example 1: A method for preparing difluorosulfurized phenyl silicone rubber, comprising:
[0044] S100, 115 parts of meta-difluorostyrene, 33 parts of reinforcing agent, 3 parts of vulcanizing agent, 9 parts of ferric oxide, 1.1 parts of structure control agent, and 4 parts of high temperature resistant agent are put into an open mill in 10 times, and the roller distance is controlled at 4 mm during mixing, and the initial rubber is obtained by mixing; in parts by weight, the structure control agent includes: 28 parts of organic silane, 50 parts of dimethyldiethoxysilane; in parts by weight, the vulcanizing agent includes: 32 parts of dipentadienyl vulcanizing agent, 40 parts of fluororubber vulcanizing agent, 8 parts of fluororubber vulcanizing agent accelerator BPP, 10 parts of 1,4-butanediamine and 10 parts of 1,6-hexanediamine ; In parts by weight, the reinforcing agent includes: 45 parts of Cabot carbon black, 55 parts of silane coupling agent LD-560; In parts by weight, the high temperature resistant agent includes: 50 parts of Lianlong antioxidant 626, 30 parts of Beijing Jiyi antioxidant 1076, and 20 parts of polytetrafluoroethylene micropowder, and the composition of the polytetrafluoroethylene micropowder is: 70wt% of particles with a particle size of 0.071mm, 10wt% of particles with a particle size of 0.063mm, 10wt% of particles with a particle size of 0.088mm, 5wt% of particles with a particle size of 0.09mm, and 5wt% of particles with a particle size of 0.1mm;
[0045] S200, after putting the primary rubber into the mold, vulcanizing it in a vulcanizer to obtain a bis(fluorobenzene)sulfide test piece with a thickness of 0.7 mm; the vulcanization temperature is 172° C., the pressure is 10 MPa, and the vulcanization time is 33 min;
[0046] S300. After the bis(fluorobenzene)sulfide test piece is coated with the adhesive, the bis(fluorobenzene)sulfide test piece and the silicone rubber compound are stacked, and after mold vulcanization, a bis(fluorobenzene)sulfide silicone-based rubber test piece with a thickness of 2.6 mm is obtained; the vulcanization temperature is 184°C, the pressure is 10 MPa, and the vulcanization time is 20 min; in parts by weight, the adhesive includes 60 parts of Chemlock 607, 30 parts of Chemlock 608 and 10 parts of Chemlock 205.
[0047] Comparative Example 2: A method for preparing difluorosulfurized phenyl silicone rubber, comprising:
[0048] S100, 115 parts of meta-difluorostyrene, 33 parts of reinforcing agent, 3 parts of vulcanizing agent, 9 parts of ferric oxide, 1.1 parts of structure control agent, and 4 parts of high temperature resistant agent are put into an open mill in 10 times, and the roller distance is controlled at 4 mm during mixing, and the primary rubber is obtained by mixing; in parts by weight, the structure control agent includes: 28 parts of organic silane, 50 parts of dimethyldiethoxysilane and 22 parts of dimethylsilyl ether; in parts by weight, the vulcanizing agent includes: 32 parts of dipentadienyl vulcanizing agent, 40 parts of fluororubber vulcanizing agent, 8 parts of fluororubber vulcanizing agent accelerator BPP, and 10 parts of 1,4-butanediamine; In parts by weight, the reinforcing agent includes: 45 parts of Cabot carbon black, 55 parts of silane coupling agent LD-560; in parts by weight, the high temperature resistant agent includes: 50 parts of Lianlong antioxidant 626, 30 parts of Beijing Jiyi antioxidant 1076, and 20 parts of polytetrafluoroethylene micropowder, and the composition of the polytetrafluoroethylene micropowder is: 70wt% of particles with a particle size of 0.071mm, 10wt% of particles with a particle size of 0.063mm, 10wt% of particles with a particle size of 0.088mm, 5wt% of particles with a particle size of 0.09mm, and 5wt% of particles with a particle size of 0.1mm;
[0049] S200, after putting the primary rubber into the mold, vulcanizing it in a vulcanizer to obtain a bis(fluorobenzene)sulfide test piece with a thickness of 0.7 mm; the vulcanization temperature is 172° C., the pressure is 10 MPa, and the vulcanization time is 33 min;
[0050] S300. After the bis(fluorobenzene)sulfide test piece is coated with the adhesive, the bis(fluorobenzene)sulfide test piece and the silicone rubber compound are stacked, and after mold vulcanization, a bis(fluorobenzene)sulfide silicone-based rubber test piece with a thickness of 2.6 mm is obtained; the vulcanization temperature is 184°C, the pressure is 10 MPa, and the vulcanization time is 20 min; in parts by weight, the adhesive includes 60 parts of Chemlock 607, 30 parts of Chemlock 608 and 10 parts of Chemlock 205.
[0051] Comparative Example 3: A method for preparing difluorosulfurized phenyl silicone rubber, comprising:
[0052] S100, 115 parts of meta-difluorostyrene, 33 parts of reinforcing agent, 3 parts of vulcanizing agent, 9 parts of ferric oxide, 1.1 parts of structure control agent, and 4 parts of high temperature resistant agent are put into an open mill in 10 times, and the roller distance is controlled at 4 mm during mixing, and the initial rubber is obtained by mixing; in parts by weight, the structure control agent includes: 28 parts of organic silane, 50 parts of dimethyldiethoxysilane and 22 parts of dimethylsilyl ether; in parts by weight, the vulcanizing agent includes: 32 parts of dipentadienyl vulcanizing agent, 40 parts of fluororubber vulcanizing agent, 8 parts of fluororubber vulcanizing agent accelerator BPP, 10 parts of 1,4-butanediamine and 10 parts of 1,6-hexanediamine; in parts by weight, the reinforcing agent includes: 45 parts of Cabot carbon black; in parts by weight, the high temperature resistant agent includes: 50 parts of Lianlong antioxidant 626, 30 parts of Beijing Jiyi antioxidant 1076, and 20 parts of polytetrafluoroethylene micropowder, and the composition of the polytetrafluoroethylene micropowder is: 70wt% of particles with a particle size of 0.071mm, 10wt% of particles with a particle size of 0.063mm, 10wt% of particles with a particle size of 0.088mm, 5wt% of particles with a particle size of 0.09mm, and 5wt% of particles with a particle size of 0.1mm;
[0053] S200, after putting the primary rubber into the mold, vulcanizing it in a vulcanizer to obtain a bis(fluorobenzene)sulfide test piece with a thickness of 0.7 mm; the vulcanization temperature is 172° C., the pressure is 10 MPa, and the vulcanization time is 33 min;
[0054] S300. After the bis(fluorobenzene)sulfide test piece is coated with the adhesive, the bis(fluorobenzene)sulfide test piece and the silicone rubber compound are stacked, and after mold vulcanization, a bis(fluorobenzene)sulfide silicone-based rubber test piece with a thickness of 2.6 mm is obtained; the vulcanization temperature is 184°C, the pressure is 10 MPa, and the vulcanization time is 20 min; in parts by weight, the adhesive includes 60 parts of Chemlock 607, 30 parts of Chemlock 608 and 10 parts of Chemlock 205.
[0055] Comparative Example 4: A method for preparing difluorosulfurized phenyl silicone rubber, comprising:
[0056] S100, 115 parts of meta-difluorostyrene, 33 parts of reinforcing agent, 3 parts of vulcanizing agent, 9 parts of ferric oxide, 1.1 parts of structure control agent, and 4 parts of high temperature resistant agent are put into an open mill in 10 times, and the roller distance is controlled at 4 mm during mixing, and the initial rubber is obtained by mixing; in parts by weight, the structure control agent includes: 28 parts of organic silane, 50 parts of dimethyldiethoxysilane and 22 parts of dimethylsilyl ether; in parts by weight, the vulcanizing agent includes: 32 parts of dipentadienyl vulcanizing agent, 40 parts of fluororubber vulcanizing agent, 8 parts of fluororubber vulcanizing agent accelerator BPP, 10 parts of 1,4-butanediamine and 10 parts of 1,6-hexanediamine; in parts by weight, the reinforcing agent includes: 45 parts of Cabot carbon black, 55 parts of silane coupling agent LD-560; in parts by weight, the high temperature resistant agent includes: 50 parts of Lianlong antioxidant 626, 20 parts of polytetrafluoroethylene micropowder, the composition of the polytetrafluoroethylene micropowder is: 70wt% of particles with a particle size of 0.071mm, 10wt% of particles with a particle size of 0.063mm, 10wt% of particles with a particle size of 0.088mm, 5wt% of particles with a particle size of 0.09mm, and 5wt% of particles with a particle size of 0.1mm;
[0057] S200, after putting the primary rubber into the mold, vulcanizing it in a vulcanizer to obtain a bis(fluorobenzene)sulfide test piece with a thickness of 0.7 mm; the vulcanization temperature is 172° C., the pressure is 10 MPa, and the vulcanization time is 33 min;
[0058] S300. After the bis(fluorobenzene)sulfide test piece is coated with the adhesive, the bis(fluorobenzene)sulfide test piece and the silicone rubber compound are stacked, and after mold vulcanization, a bis(fluorobenzene)sulfide silicone-based rubber test piece with a thickness of 2.6 mm is obtained; the vulcanization temperature is 184°C, the pressure is 10 MPa, and the vulcanization time is 20 min; in parts by weight, the adhesive includes 60 parts of Chemlock 607, 30 parts of Chemlock 608 and 10 parts of Chemlock 205.
[0059] Comparative Example 5: A method for preparing difluorosulfurized phenyl silicone rubber, comprising:
[0060] S100, 115 parts of m-difluorostyrene, 33 parts of reinforcing agent, 3 parts of vulcanizing agent, 9 parts of ferric oxide, 1.1 parts of structure control agent, and 4 parts of high temperature resistant agent are put into an open mill in 10 times, and the roller distance is controlled at 4 mm during mixing, and the primary rubber is obtained by mixing; in parts by weight, the structure control agent includes: 28 parts of organic silane, 50 parts of dimethyldiethoxysilane and 22 parts of dimethylsilyl ether; in parts by weight, the vulcanizing agent includes: 32 parts of dipentadienyl vulcanizing agent, 40 parts of fluororubber vulcanizing agent, 8 parts of fluororubber vulcanizing agent accelerator BPP, 1 0 parts of 1,4-butanediamine and 10 parts of 1,6-hexanediamine; in parts by weight, the reinforcing agent includes: 45 parts of Cabot carbon black, 55 parts of silane coupling agent LD-560; in parts by weight, the high temperature resistant agent includes: 50 parts of Lianlong antioxidant 626, 30 parts of Beijing Jiyi antioxidant 1076, and 20 parts of polytetrafluoroethylene micropowder, and the composition of the polytetrafluoroethylene micropowder is: 70wt% of particles with a particle size of 0.071mm, 15wt% of particles with a particle size of 0.063mm, and 15wt% of particles with a particle size of 0.088mm;
[0061] S200, after putting the primary rubber into the mold, vulcanizing it in a vulcanizer to obtain a bis(fluorobenzene)sulfide test piece with a thickness of 0.7 mm; the vulcanization temperature is 172° C., the pressure is 10 MPa, and the vulcanization time is 33 min;
[0062] S300. After the bis(fluorobenzene)sulfide test piece is coated with the adhesive, the bis(fluorobenzene)sulfide test piece and the silicone rubber compound are stacked, and after mold vulcanization, a bis(fluorobenzene)sulfide silicone-based rubber test piece with a thickness of 2.6 mm is obtained; the vulcanization temperature is 184°C, the pressure is 10 MPa, and the vulcanization time is 20 min; in parts by weight, the adhesive includes 60 parts of Chemlock 607, 30 parts of Chemlock 608 and 10 parts of Chemlock 205.
[0063] Comparative Example 6: A method for preparing difluorosulfurized phenyl silicone rubber, comprising:
[0064] S100, 115 parts of m-difluorostyrene, 33 parts of reinforcing agent, 3 parts of vulcanizing agent, 9 parts of ferric oxide, 1.1 parts of structure control agent, and 4 parts of high temperature resistant agent are put into an open mill in 10 times, and the roller distance is controlled at 4 mm during mixing, and the initial rubber is obtained by mixing; in parts by weight, the structure control agent includes: 28 parts of organic silane, 50 parts of dimethyldiethoxysilane and 22 parts of dimethylsilyl ether; in parts by weight, the vulcanizing agent includes: 32 parts of dipentadienyl vulcanizing agent, 40 parts of fluororubber vulcanizing agent, 8 parts of fluororubber vulcanizing agent accelerator BPP, 10 parts of 1,4-butanediamine and 10 parts of 1,6 -hexanediamine; in parts by weight, the reinforcing agent includes: 45 parts of Cabot carbon black, 55 parts of silane coupling agent LD-560; in parts by weight, the high temperature resistant agent includes: 50 parts of Lianlong antioxidant 626, 30 parts of Beijing Jiyi antioxidant 1076, and 20 parts of polytetrafluoroethylene micropowder, and the composition of the tetrafluoroethylene micropowder is: 70wt% of particles with a particle size of 0.071mm, 10wt% of particles with a particle size of 0.063mm, 10wt% of particles with a particle size of 0.088mm, 5wt% of particles with a particle size of 0.09mm, and 5wt% of particles with a particle size of 0.1mm;
[0065] S200, after putting the primary rubber into the mold, vulcanizing it in a vulcanizer to obtain a bis(fluorobenzene)sulfide test piece with a thickness of 0.7 mm; the vulcanization temperature is 172° C., the pressure is 10 MPa, and the vulcanization time is 33 min;
[0066] S300. After the benzene fluoride sulfide test piece is coated with the adhesive, the benzene fluoride sulfide test piece is stacked with the silicone rubber compound, and after mold vulcanization, a benzene fluoride sulfide silicone-based rubber test piece with a thickness of 2.6 mm is obtained; the vulcanization temperature is 184°C, the pressure is 10 MPa, and the vulcanization time is 20 min; in parts by weight, the adhesive includes 60 parts of Chemlock 607 and 10 parts of Chemlock 205.
[0067] Test 1: The high temperature resistance performance of the difluorosulfurized phenyl silicone rubber prepared according to the preparation methods of Examples 1-3 and Comparative Examples 1-6 was tested, and the high temperature resistance performance of the device was tested after it was used in the screw pump sealing device. Rubber high temperature resistance test method: After aging for 120 hours under constant temperature conditions, the deformation amount (%) and strength (MPa) were detected. The high temperature resistance performance test of the screw pump sealing device includes the leakage volume (ml) after static 10MPa compression for 120 hours and the seal failure time (h) under dynamic 7MPa and 100r / min conditions. The capping time during the test was 168h. The test results are shown in Table 1 and Table 2 respectively.
[0068] Table 1
[0069]
[0070]
[0071] It can be seen from the test data of Examples 1-3 that the difluorosulfurized phenyl silicone-based rubber seal provided by the present invention has good high temperature resistance.
[0072] From the comparison between Comparative Example 1 and Example 3, it can be seen that the use of the structure control agent provided by the present invention can improve the high temperature resistance of the product.
[0073] From the comparison between Comparative Example 2 and Example 3, it can be seen that the use of the vulcanizing agent provided by the present invention can improve the high temperature resistance of the product.
[0074] From the comparison between Comparative Example 3 and Example 3, it can be seen that the use of the reinforcing agent provided by the present invention can improve the high temperature resistance of the product.
[0075] From the comparison between Comparative Example 4 and Example 3, it can be seen that the high temperature resistant agent provided by the present invention can improve the high temperature resistance of the product.
[0076] From the comparison between Comparative Example 5 and Example 3, it can be seen that the high temperature resistance of the product can be improved by using the tetrafluoroethylene powder particle size ratio provided by the present invention.
[0077] From the comparison between Comparative Example 6 and Example 3, it can be seen that the use of the adhesive provided by the present invention can improve the high temperature resistance of the product.
[0078] Table 2
[0079]
[0080] It can be seen from the test data of Examples 1-3 that the difluorosulfurized phenyl silicone rubber seal can operate for more than 168 hours at a temperature of 250° C., and can meet the requirements of deep shale gas drilling operations.
[0081] From the comparison between comparative examples 1-6 and embodiment 3, it can be seen that the selection of reinforcing agent, vulcanizing agent, structure control agent, high temperature resistant agent, binder and the compounding of polytetrafluoroethylene powder particle size can improve the service life of the seal in deep shale gas drilling operations.
[0082] Experiment 2: The hydrogen sulfide resistance of the bis-fluorosulfurized phenyl silicone rubber prepared according to the preparation methods of Examples 1-3 and Comparative Examples 1-6 was tested: The sealing parts made of bis-fluorosulfurized phenyl silicone rubber were placed in a static atmosphere with a concentration of 5 mg / m 3 After 120h under H2S environment, the deformation (%) and strength (MPa) were tested again. The test results are shown in Table 3.
[0083] Table 3
[0084]
[0085] It can be seen from the test results of Examples 1-3 that the seal made of the difluorosulfurized phenyl silicone rubber provided by the present invention has good resistance to hydrogen sulfide.
[0086] From the comparison between comparative examples 1-6 and embodiment 3, it can be seen that the selection of reinforcing agent, vulcanizing agent, structure control agent, high temperature resistant agent, binder and the compounding of polytetrafluoroethylene micropowder particle size can improve the hydrogen sulfide resistance of difluorosulfurized phenyl silicone rubber.
[0087] Test 3: The relative wear index (%) of the difluorosulfurized phenyl silicone rubber prepared according to the preparation methods of Examples 1-3 and Comparative Examples 1-6 was tested according to GB / T 9867-200. The test results are shown in Table 4.
[0088] Table 4
[0089]
[0090] From the test data of Examples 1-3, it can be seen that the bis(fluorinated)silicone-based rubber has good wear resistance and is less affected by temperature below 250°C, which can meet the requirements of drilling fluid density of 1.8-2.2 g / cm 3 , required for on-site operations with high solid content.
[0091] From the comparison between comparative examples 1-6 and embodiment 3, it can be seen that the selection of reinforcing agent, vulcanizing agent, structure control agent, high temperature resistant agent, binder and the compounding of polytetrafluoroethylene micropowder particle size can improve the hydrogen sulfide resistance of difluorosulfurized phenyl silicone rubber.
[0092] Test 4: In the process of deep shale gas drilling, in order to ensure sufficient sand carrying capacity of the drilling fluid and a high mechanical drilling speed, the horizontal section adopts large displacement, high pump pressure, and high drilling pressure, which has a greater impact on the rotary percussion drilling tool, especially the seal, and has a greater impact on the service life of the screw drilling tool. According to GB / T1843-2008 and field conditions, the impact resistance of the double fluorosulfurized phenyl silicone rubber prepared by the preparation method of Examples 1-3 and Comparative Examples 1-6 was tested. According to the actual drilling parameters on site, the displacement is 30-38L / s, the drilling pressure is 85-165kN, the ground speed is 70-120r / min, and the screw pressure difference is 4-7MPa. The designed impact speed is 2.0m / s and the impact is continuously performed 100 times. The bifluorosulfurized phenyl silicone-based rubber prepared in Examples 1-3 is not damaged in the A-type notch test and the B-type notch test. The bifluorosulfurized phenyl silicone-based rubber prepared in Comparative Examples 1-6 is not slightly or seriously damaged in the A-type notch test and the B-type notch test, indicating that the seal made of the bifluorosulfurized phenyl silicone-based rubber of the present invention has good impact resistance.
[0093] Field test of high-efficiency rotary percussion drilling tools: 3 wells were tested in Sichuan and Chongqing, with a total footage of 6,823 meters in the deep well section. The average number of trips in the deep well section decreased from 6.87 to 4.55, and the average use time of rotary percussion drilling tools increased from 86 hours / tool to 172 hours / tool. There were no problems such as leakage, debonding, stalling, shaft breakage, and braking of rotary percussion drilling tools. In addition, the ground cooling system of drilling fluid can be reduced or not used, which improves the timeliness and efficiency of the operation. Based on the single consideration of the electric screw operation time based on the number of trips saved, the average drilling cycle in the same area was saved by 2.68 days, the average drilling cycle in the deep well section was reduced by 8.12 days, and the complex accident rate in the deep well section was reduced from 2.68% to 1.52%.
[0094] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A bis(fluorosulfurized) phenyl silicone rubber, characterized in that: The molecular weight of difluorosulfurized phenyl silicone rubber is 8000-12000, the fluorine content is 1.4%-2.0%, the phenyl content is 18%-24%, and the hydrogen content is 2.1%-3.0%; The molecular structure of the difluorosulfurized phenyl silicone rubber is shown in (I), wherein n in formula (I) is 16-25 and m is 13-20; 2. The bis(fluorosulfurized) phenylsilicone-based rubber according to claim 1, characterized in that: The fluorine content of the difluorosulfurized phenyl silicone rubber is 1.7%, the phenyl content is 21% and the hydrogen content is 2.6%.
3. A method for preparing the difluorosulfurized phenyl silicone rubber according to claim 1 or 2, characterized in that: include: S100, 110-120 parts of m-difluorostyrene, 30-35 parts of reinforcing agent, 2-5 parts of vulcanizing agent, 8-10 parts of ferric oxide, 1-1.2 parts of structure control agent, and 3-5 parts of high temperature resistant agent are added into an open mill several times, and mixed to obtain a primary rubber; S200, vulcanizing the pre-made rubber in a vulcanizer to obtain a difluorobenzene sulfide test piece; S300, after the benzene bis(fluorosulfide) test piece is coated with an adhesive, the benzene bis(fluorosulfide) test piece is stacked with a silicone rubber compound, and the benzene bis(fluorosulfide) silicone-based rubber is obtained after mold closing and vulcanization.
4. The preparation method according to claim 3, characterized in that: The vulcanization conditions in S200 are as follows: the vulcanization temperature is 165-180° C., the pressure is 8-12 MPa, and the vulcanization time is 30-35 min.
5. The preparation method according to claim 3, characterized in that: The vulcanization conditions in S300 are as follows: the vulcanization temperature is 175-195° C., the pressure is 8-12 MPa, and the vulcanization time is 18-23 min.
6. The preparation method according to claim 3, characterized in that: In parts by weight, the binder includes 55-65 parts of Chemlock 607, 25-35 parts of Chemlock 608 and 5-15 parts of Chemlock 205.
7. The preparation method according to any one of claims 3 to 6, characterized in that: In parts by weight, the structure control agent comprises: 25-30 parts of organic silane, 45-55 parts of dimethyldiethoxysilane and 20-24 parts of disodium silyl ether.
8. The preparation method according to claim 7, characterized in that: In parts by weight, the vulcanizing agent includes: 30-35 parts of dipentadienyl vulcanizing agent, 38-42 parts of fluororubber vulcanizing agent, 7-9 parts of fluororubber vulcanizing agent accelerator BPP, 8-12 parts of 1,4-butanediamine and 8-12 parts of 1,6-hexanediamine.
9. The preparation method according to claim 7, characterized in that: In parts by weight, the reinforcing agent includes: 40-50 parts of carbon black and 50-60 parts of silane coupling agent.
10. The preparation method according to claim 7, characterized in that: In parts by weight, the high temperature resistant agent includes: 45-55 parts of antioxidant 626, 25-35 parts of antioxidant 1076, and 18-24 parts of polytetrafluoroethylene powder.